1999
DOI: 10.1099/0022-1317-80-12-3137
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of cattle with a DNA plasmid encoding the bovine viral diarrhoea virus major glycoprotein E2

Abstract: Bovine viral diarrhoea virus (BVDV) is an economically important pathogen of cattle that is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…However, there is concern that neither of these traditional types of vaccine is optimal for controlling BVDV infection (48). For that reason, the possibility of using immunodominant proteins of BVDV in the form of DNA (23,24,(35)(36)(37) or protein subunit (6,9,10) vaccines has gained widespread interest. The use of protein and DNA vaccines provides an opportunity to introduce vaccines that are arguably the safest vaccines that can be developed.…”
mentioning
confidence: 99%
“…However, there is concern that neither of these traditional types of vaccine is optimal for controlling BVDV infection (48). For that reason, the possibility of using immunodominant proteins of BVDV in the form of DNA (23,24,(35)(36)(37) or protein subunit (6,9,10) vaccines has gained widespread interest. The use of protein and DNA vaccines provides an opportunity to introduce vaccines that are arguably the safest vaccines that can be developed.…”
mentioning
confidence: 99%
“…In recent years, several research teams have reported DNA immunisation to BVDV structural proteins in the mouse [26,42,45,46] and cattle [27,47,42]. All experiments involved E2 constructs from a single BVDV-1a viral strain.…”
Section: Discussionmentioning
confidence: 99%
“…In most reports, cross-neutralisation with strains from other genotypes was not tested. Harpin et al [26,27] showed that 3 / 4 vaccinated mice cross-neutralised BVDV-1b strain New-York as well as BVDV-1a NADL but not BVDV-2 strain 125, indicating that cross-neutralisation is restricted to the genotype from which the coding sequence had been cloned. Another report by Nobiron et al [46] showed that the response to heterologous strain NADL was much lower in terms of titres and numbers of responding mice than to homologous strain Ky1203nc though both belong to the same genotype Ia.…”
Section: Discussionmentioning
confidence: 99%
“…A BVDV-la DNA vaccine induced neutralising antibody response and cell-mediated immune response in cattle but gave a limited protection against a heterologous BVDV-lb strain (36).…”
Section: Protective Efficacy Of Current Bvdv Vaccinesmentioning
confidence: 99%